2011
DOI: 10.1177/00333549111260s204
|View full text |Cite
|
Sign up to set email alerts
|

How Parents' Negative Experiences at Immunization Visits Affect Child Immunization Status in a Community in New York City

Abstract: Objective. Little is known about how families' experiences with immunization visits within the medical home may affect children's immunization status. We assessed the association between families' negative immunization experiences within the medical home and underimmunization.Methods. We surveyed parents (n5392) of children aged 2-36 months about immunization experiences at community health centers, hospital-based clinics, private practices, and community-based organizations in New York City. We used Chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 27 publications
2
14
0
3
Order By: Relevance
“…In addition to questions adapted from the 2003 National Survey of Children's Health, we added variables previously used in the published medical literature to comprehensively measure presence of key elements of the medical home [21,24]. These elements were further categorized into domains of the medical home as defined by the American Academy of Pediatrics, including accessibility, continuity, comprehensiveness, family-centeredness, compassion, cultural effectiveness [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to questions adapted from the 2003 National Survey of Children's Health, we added variables previously used in the published medical literature to comprehensively measure presence of key elements of the medical home [21,24]. These elements were further categorized into domains of the medical home as defined by the American Academy of Pediatrics, including accessibility, continuity, comprehensiveness, family-centeredness, compassion, cultural effectiveness [28].…”
Section: Methodsmentioning
confidence: 99%
“…A secondary data analysis was performed using a dataset obtained from a bilingual cross-sectional survey administered during May 2007-June 2008 to assess the influence of parental interactions with the medical home on child immunization status [21].…”
Section: Design/study Populationmentioning
confidence: 99%
“…We speculated that education is an intermediate factor that affects other vaccine acceptance-related factors [11]. Previous studies also demonstrated that education could be a promoter [19][20][21][22] or a barrier [23][24][25] for a vaccination. We found that education attainment was correlated with knowledge regarding to EVD.…”
Section: Discussionmentioning
confidence: 98%
“…21 Sadece erişkinlerde kullanılan bir bölge olan dorsogluteal bölgeye gluteal arter yakınlığından dolayı aspirasyonun gerekli olduğu, fakat diğer bölgeler için aspirasyonun gerekli olmadığı belirtilmektedir. 2,19,[22][23][24][25] Bağışıklama Danışma Komitesi "aspirasyon sonrasında enjektöre kan gelmemesinin enjeksiyonun doğru şekilde yapıldığının bir göstergesi olmadığını", üstelik çocuklarda önerilen enjeksiyon bölgesinde büyük kan damarlarının olmaması nedeni ile de ağ-rıya neden olabilen bir uygulama olduğunu ifade etmektedir. 7,[21][22][23] Ipp.…”
Section: Aspi̇rasyon Yapmaunclassified
“…Olumsuz aşılama deneyimi yaşayan çocukların daha sonraki enjeksiyon uygulamalarında enjeksiyona karşı güçlü olumsuz tepki gösterdiği de belirlenmiştir. 25,27 Yenidoğan döneminde, ağrılı işlemlerde pozisyon verme ve emzirme gibi fiziksel rahatlama yöntemleri uygulama kolaylığı ve etkinliği nedeni ile idealdir. 2,7,26 Harrington ve ark.nın, 230 bebeği içeren çalışmasında; gevşek kundaklama, yan/yüz-üstü pozisyonu, pışpışlama, hafifçe sallama ve emzirme gibi fiziksel uygulamaların 2-4 aylık bebeklerde aşı sonrası ağrı skorlarının ve ağlama-nın azalmasına yol açtığı belirlenmiştir.…”
Section: Farmakoloji̇k Olmayan Uygulamalar Yenidoğan Bebek Ve Küçük çunclassified